Technologys of confectionery products gluten-free in restaurants - Sylka, Iryna; Stukalska (Ivanova), Nataliia (My University, 2020)
Celiac disease - it is a disorder that damages your small intestine and keeps it from absorbing the nutrients in food. The damage to your intestinal tract is caused by your immune system's reaction to gluten. Therefore, today there is a prospect of improving or developing recipes for different groups of dishes with the replacement of wheat flour. This is especially true of flour confectionery, which is popular among various groups. Expanding the range of flour and confectionery products based on corn flour is relevant.
Keywords: gluten; confectionery; flour; глютен; кондитерські вироби; борошно; кафедра технології ресторанної і аюрведичної продукції